Validación del modelo de cultivo DSSAT CERES-Maize para simular rendimientos de maíz blanco bajo condiciones de cambio climático futuro en el sector la Argelia, Loja - Zapata Cartuche, María Fernanda (2024)
The DSSAT CERES-Maize crop simulation model simulates the growth and development of maize, which has been widely used for studies on the impacts of climate variability and change. The objective of this work was to determine the effect of future climate change on white corn yields using the DSSAT CERES-Maize model calibrated and validated under the environmental conditions of Loja. For this purpose, model validation was performed using information from field trials conducted in 2018-2019 and 2020-2021 under different planting density and nutrition treatments. Once the model was validated, 5 climate models (GFDL, IPSL, MPIE, MRIE, UKES) were used under 3 climate change scenarios (ssp126, ssp370, ssp585) for the periods 2041-2060 and 2081-2100. The genetic coefficients that best matched the phenology and yield of INIAP 103 maize variety “Mishqui Sara” were P1:255 °C; P5: 820 °C; G2:420 g; G3: 9 mg/day and PHINT: 68.30 °C. The model simulated excellent RMSEP at the anthesis stage (0.90 % and 0.85 %), physiological maturity (6.22 % and 5.97 %) and yield (5.56 % and 8.96 %) in calibration and validation, respectively. In the results of the simulations under different greenhouse gas emissions scenarios (ssp126, ssp370 and ssp585), the average yield of white corn will increase by 2.14 % in the ssp126 scenario (low CO2 emissions), while, a reduction of 14.86 % in the ssp370 scenario (medium CO2 emissions) and 2.84 % in the ssp585 scenario (high CO2 emissions) is predicted for the period 2041-2060. For the period 2081-2100, average white corn yields could increase by 4.01 % in ssp126, but are projected to decrease by 17.65 % and 20.18 % at higher GHG emissions, ssp370 and ssp585, respectively. As for the projections of variation in the phenological cycle of corn, the vegetative and reproductive phases will be reduced under different scenarios of greenhouse gas emissions (ssp126, ssp370 and ssp585) with variations between 25% and 38% reduction in its total cycle in the two periods evaluated. These results indicate that adaptation measures for white corn cultivation should be implemented, such as mitigation strategies and sustainable agricultural practices to counteract the negative effects of climate change.